Upaya Kaum Awam dalam Menemukan Jati Diri Menurut Himbauan Apostolik Christifideles Laici No. 57-63 - Mawarni Gea; Alexius Poto Obe; Petra Opi Pasrani Hulu (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
This writing originates from the author's concerns or the reality of the laity's unawareness of their identity or existence as members of the Church. The author sees a lack of involvement of the laity both within the Church and outside the Church. The main issues raised by the author are who lay people are and how a lay believer finds his or her identity as a true Catholic both within the Church and outside the Church. The purpose of this writing is to deepen the understanding of lay people finding their identity as well as their duties and involvement. Meanwhile, the method used in this thesis is literature review, namely studying the theme of this thesis by utilizing ideas and discussions from books, journals, encyclopedias, Church documents, the internet and other literature. The results of the discussion obtained are that lay people are all Christian believers except those classified as priests or religious recognized by the Church. So, Christian believers who, thanks to baptism, have become God's people in their own way share in carrying out the priestly, prophetic and royal duties of Christ. The characteristic of the laity is their worldly nature. Lay people are invited to be more active and committed in carrying out their vocation, both in the internal life of the Church and the world, bringing a positive impact and Christian values ​​in all aspects of life.